Kendalikan Diri atau Ikuti Tren? Pengaruh Bandwagon Effect dan Self-Control Terhadap Perilaku Konsumtif Berbelanja di Media Sosial - Putri, Salsabila Atika; Wibowo, Moersito Wimbo (Universitas Muhammadiyah Metro, 2025)
Social media has become a platform that influences people's lifestyles and consumption patterns. Consumerist behavior is often triggered by various psychological factors, such as the bandwagon effect, where individuals are driven to follow trends to feel accepted and self-control, which plays a crucial role in managing impulsive consumption.This study is a quantitative research that aims to analyze the influence of the bandwagon effect and self-control on consumerist shopping behavior on social media. Data collection was conducted through a questionnaire survey targeting Generation Z, with a total of 280 respondents participating in this study. The collected data was processed and tested using the Normality Assumption Test and Regression Test. The results show that the bandwagon effect (X1) has a positive and significant impact on consumerist behavior (Y), where the tendency to follow trends or others' actions encourages individuals to make purchases without deep consideration. Meanwhile, self-control (X2) is found to have a negative and stronger influence on consumerist behavior (Y) compared to the bandwagon effect (X1). Individuals with high levels of self-control are able to manage impulses, resist external pressure, and make more rational decisions, leading to lower consumerist behavior. These findings indicate that self-control (X2) plays a crucial role in mitigating the negative effects of the bandwagon effect (X1), especially in the context of online shopping on platforms like TikTok.